Titanium Elastic Nailing in Adult Humerus Diaphyseal Fracture (Medical Forum Monthly, 2024)
Objective: To study the union,joint stifness,deformity and incidence of infection after humerus diaphyseal fracture.Study Design: Quasi experimental prospective study.Place and Duration of Study: This study was conducted at the Sheikh Khalifa Bin Zayed Al-Nahyan Hospital Rawlakot Azad Kashmir from 01.08.2016 to 01.08.2017.Materials and Methods: Thirty patients of either gender with age range between 18 years to 65 years with closed diaphyseal humerus fracture were included in study. Titanium elastic nailing was used to treat these patients. Outcome was measured in terms of union, infection rate, angulation and range of motion at shoulder and elbow joints.Results: 30 patients were operated including 21 male and 9 female. We observed union in 23 patients. 07 patients had superficial infection around the margins of protuberant nail while 2 patients developed deep infection. Among the united fractures all patient had angulation in acceptable range. Seven patients who had delayed union or non-union showed limitation of range of movement at shoulder and elbow joints.Conclusion: Adult humrus fracture fixed percutaneously takes less time,losses less blood,disrupts minimum tissue and the healing is natural. Selection criteria and procedure expertise make the best results outcome for this method and should be strictly observed.